(untitled) (Global Journal of Medical Research, 2015)
Background: Use of contraceptive methods is one of the efficacious interventions that help to prevent HIV transmission and unintended pregnancies among HIV positive women. However, contraceptive utilization, in general, and Long Acting and Permanent Contraceptive (LAPM) methods, in particular, and its integration with HIV treatment services is not well understood in poor-resource settings. The study aimed to assess the level of integration of LAPM with ART, LAPM utilization and associated factors among HIV positive women in public hospitals of Tigray, northern Ethiopia. Methods: A cross-sectional study was conducted in 2013 among 343 HIV positive married women selected using two-stage cluster sampling.